KEBIJAKAN DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) DALAM PEMBERIAN PERIZINAN SELAMA PANDEMI COVID-19 - Ikhfa Pratiwi; Amiludin Amiludin; Muhammad Asmawi (Universitas Muhammadiyah Tangerang, 2021)
Business licensing is very necessary in achieving the performance of providers or providers of quality public services for Regional Development so that the Regional Government is responsible and responsive to the needs of the community in fulfilling and equitable economic and political equality. However, due to the Covid-19 Pandemic in Indonesia, all sectors were affected. This research focuses on knowing the role of the Investment Service and One Stop Integrated Services in granting building permits as a target for local revenue during the Covid-19 pandemic. There has been a decrease in the number of applicants for building permits to build up to 50%. The Target of Original Regional Income before the Covid-19 pandemic was 52 billion, when the Covid-19 pandemic the target of Regional Original Income had been reduced by 50%, accounting for 26 billion. The target of Regional Original Income in June has been reached up to 40%. This is in achieving the target of Regional Original Income that will be focused on the budget for purchasing medical devices and the development budget for 2020 will be abolished for a moment, only urgent development can be implemented.Keywords: Role, Building Construction Permit, Regional Original Income.